Technology-enhanced learning and linguistic diversity : strategies and approaches to teaching students in a 2nd or 3rd language - Mather, Patrick-André (Emerald studies in higher education, innovation and technology., 2020)
Educators in Europe and the Americas traditionally have little formal training in applied linguistics, and yet they are increasingly faced with a growing multilingual student base. This book responds to the need to make the university community more aware of the unique experience of linguistically diverse students. Drawing on research and hands-on experience from both linguists and non-linguists who deal with students from different language backgrounds in their classroom, this book includes contributions which include linguistic research on 2nd and 3rd language acquisition, as well as case studies of specific challenges in teaching content courses in various disciplines, to offer a roadmap of how educators might facilitate the learning of their bilingual student cohort. Combining issues that have been studied separately within the fields of theoretical linguistics, pedagogy and information and communication technologies (ICT), the author presents a comprehensive overview across the areas of applied linguistics, foreign language teaching methodologies and technological tools to address multilingualism within the university classroom, and ultimately equip educators to meet a critical demand.